Dissociation Rate of THF-methane Hydrates - GIAVARINI, Carlo; MACCIONI, Filippo; SANTARELLI, Maria Laura (Petroleum Science and Technology, 2008)
A number of papers and research projects suggest that stranded natural gas can be transported in a solid hydrate state at higher temperatures or lower pressures compared to conventional transportation systems (LNG and CNG). The self-preservation effect of methane hydrate can probably be improved by the use of a third component besides CH4 and water. Tetrahydrofuran (THF) is a promoter that greatly reduces the required formation pressures. In the present work the influence of THF on the decomposition kinetics of mixed THF-CH4 hydrates was studied to evaluate the THF stabilization effect. The experimental work, carried out with the help of a reaction calorimeter, has revealed that the dissociation rate of mixed THF hydrates is lower (on average by one order of magnitude) than that of simple methane hydrates. Mixed hydrates can also be stored for short periods at temperatures over 0ıC. However, the best preservation conditions (among the experimented ones) are realized at 1ıC and 3 MPa. (about 66 days required for complete dissociation).